Optimized Analytical Study to Show the Impact of CFO on the Performance of LTE Uplink (International Journal of Engineering and Computer Science, 2018)
Although tremendous progress has been made in the past decade on wireless communications domain, but still the impact of carrier frequency offset (CFO) on system performance especially on orthogonal frequency division multiplexing (OFDM) is an area of concern. As reported in the literature the conventional research works shows that the carrier frequency offset (CFO) occurs mainly due to oscillator instability and Doppler shift introduced in the channel. In this paper, the impact of carrier frequency offset (CFO) on the system performance is discussed and the impact of the carrier frequency offset (CFO) drawback even worse in uplink scenario where every user experiences the different offset because of random nature of users. The usage of DFT based SC-FDMA over IFFT based OFDM shows good impact on system uplink scenario where DFT based SC-FDMA is free of PAPR which is common problem in IFFT based OFDM system as mobile handsets have limited battery power. Finally the Bit error graphs and constellation diagrams in the results section reveals the fact that the CFO impact on the system uplink is so severe that in order to save the user integrity data suppression techniques needs to be employed in an efficient way.